2011
DOI: 10.1007/s00167-010-1375-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular stabilization following anterior cruciate ligament injury in children and adolescents

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…An accurate understanding of the athlete' s physical maturity by determining skeletal age and Tanner stage helps to identify which treatment is best for a specific patient. 73,86,87,[92][93][94][95][96][97][98] The most common method of measuring the patient' s skeletal age is to compare an anteroposterior radiograph of the patient' s left hand and wrist to an age-specific radiograph in the Greulich and Pyle atlas. 94 Tanner stage can be determined by self-assessment, which has been shown to be valid and reliable.…”
Section: Treatmentmentioning
confidence: 99%
“…An accurate understanding of the athlete' s physical maturity by determining skeletal age and Tanner stage helps to identify which treatment is best for a specific patient. 73,86,87,[92][93][94][95][96][97][98] The most common method of measuring the patient' s skeletal age is to compare an anteroposterior radiograph of the patient' s left hand and wrist to an age-specific radiograph in the Greulich and Pyle atlas. 94 Tanner stage can be determined by self-assessment, which has been shown to be valid and reliable.…”
Section: Treatmentmentioning
confidence: 99%
“…A number of series' report transphyseal ACL reconstructions using a variety of grafts and fixation devices with good outcomes in pediatric patients and little risk of growth disturbance [8,10,[50][51][52][53][54][55], [56•], [57], [58•]. Aronowitz et al [50] used Achilles tendon allograft with 9-10 mm tunnels in patients with a skeletal age of at least 14.…”
Section: Transphyseal Techniquesmentioning
confidence: 99%
“…Five patients were Tanner stage I or II, 21 were Tanner stage III or IV and there were no reported growth or angular deformities. Nikolaou et al [57] reported the results of 94 transphyseal hamstring reconstructions in patients followed to skeletal maturity. Of these patients 66 were Tanner stage I or II.…”
Section: Transphyseal Techniquesmentioning
confidence: 99%
“…Studies in adult patients [7,8,24,39] and in pediatric patients [12,28,32] have shown an increased incidence of medial meniscal tears with delayed ACL reconstruction. Although the treatment of ACL tears in skeletally immature patients remains controversial [33], the risk of physeal injury and resulting growth disturbance from ACL repair to a patient with open physes is now thought to be small [15,22], and many centers (including our institution) opt for prompt reconstruction before skeletal maturity [9,16,20,25,31,34,40].…”
Section: Introductionmentioning
confidence: 99%